2013
DOI: 10.4111/kju.2013.54.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Acute Epididymitis in Children: the Role of the Urine Test

Abstract: PurposeAcute epididymitis is considered to have an important role in children with scrotal pain. Recent reports have shown that urinalysis is not helpful for the diagnosis and treatment of acute epididymitis owing to negative microbiological findings. Therefore, we analyzed clinical and laboratory characteristics to examine the diagnostic yield of urinalysis in children.Materials and MethodsWe retrospectively reviewed the medical records of 139 patients who were diagnosed with acute epididymitis from 2005 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 17 publications
1
25
0
2
Order By: Relevance
“…Urinalysis in the setting of an acute scrotum is for the identification of pyuria as a potential marker for infectious epididymitis, which may occur secondary to retrograde flow of infected urine from the urethra through the ejaculatory ducts and vas deferens into the epididymis . Previous studies have demonstrated that most pediatric males with epididymitis do not have pyuria on urinalysis or a positive urine culture and, therefore, do not require routine antibiotic treatment . As there are no clear predictors for males with a bacterial etiology of epididymitis the general recommendation is for a urine culture to be performed on males with epididymitis, while the utility of a screening urinalysis for pyuria is less clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinalysis in the setting of an acute scrotum is for the identification of pyuria as a potential marker for infectious epididymitis, which may occur secondary to retrograde flow of infected urine from the urethra through the ejaculatory ducts and vas deferens into the epididymis . Previous studies have demonstrated that most pediatric males with epididymitis do not have pyuria on urinalysis or a positive urine culture and, therefore, do not require routine antibiotic treatment . As there are no clear predictors for males with a bacterial etiology of epididymitis the general recommendation is for a urine culture to be performed on males with epididymitis, while the utility of a screening urinalysis for pyuria is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that most pediatric males with epididymitis do not have pyuria on urinalysis or a positive urine culture and, therefore, do not require routine antibiotic treatment . As there are no clear predictors for males with a bacterial etiology of epididymitis the general recommendation is for a urine culture to be performed on males with epididymitis, while the utility of a screening urinalysis for pyuria is less clear. In our study cohort urinalysis was performed in 86% of males without testicular torsion and 0% in males with torsion.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that epididymitis may be isolated to the body or the tail and can be missed if these structures 7,10,11,12 Among patients with orchalgia, 12 (14.45%) patients had hydrocele in our study.…”
Section: Discussionmentioning
confidence: 64%
“…One prior study specifically evaluated the utility of the UA in pediatric patients with epididymitis. 17 It found that pyuria and positive urine cultures were rare in pediatric epididymitis. The authors recommended that a UA and urine culture be routinely performed as antibiotics can be withheld unless there is pyuria or a positive urine culture.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommended that a UA and urine culture be routinely performed as antibiotics can be withheld unless there is pyuria or a positive urine culture. 17 The question of whether or not to give antibiotics to pediatric patients with epididymitis is important, but this study asks an even more basic question: is UA needed at all for evaluating patients with scrotal pain (and possible epididymo-orchitis)?…”
Section: Discussionmentioning
confidence: 99%